2003
DOI: 10.1128/iai.71.2.1001-1007.2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expression of the Borrelia burgdorferi β 3 -Chain Integrin Ligand, P66, in Ticks and in Culture

Abstract: Borrelia burgdorferi is maintained in an infection cycle between mammalian and arthropod hosts. Appropriate gene expression by B. burgdorferi at different stages of this cycle is probably essential for transmission and establishment of infection. The B. burgdorferi ␤ 3 integrin ligand P66 is expressed by the bacteria in mammals, laboratory culture, and engorged but not unfed ticks. No in vitro culture conditions in which P66 expression reflected that in the unfed tick were found, suggesting that there are aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…2B, ␣-P66, lanes 1, 2, and 3; all strains). These observations were consistent with those of a previous study where it was demonstrated that the levels of P66 were not affected by either temperature, pH, or a combination of these factors (14). The above analysis also suggests that the loss of expression of BBA64 did not affect other critical determinants which are known to play a role in the infectious process, albeit this analysis was limited to OspC and P66.…”
Section: Construction Of the Bba64 Mtsupporting
confidence: 82%
“…2B, ␣-P66, lanes 1, 2, and 3; all strains). These observations were consistent with those of a previous study where it was demonstrated that the levels of P66 were not affected by either temperature, pH, or a combination of these factors (14). The above analysis also suggests that the loss of expression of BBA64 did not affect other critical determinants which are known to play a role in the infectious process, albeit this analysis was limited to OspC and P66.…”
Section: Construction Of the Bba64 Mtsupporting
confidence: 82%
“…In contrast to invasin, a ␤ 1 integrin ligand of Yersinia pseudotuberculosis, P66 would not be expected to promote uptake of the bacteria by mammalian cells, as there is no current evidence that B. burgdorferi occupies an intracellular niche during mammalian infection. The significance of P66 is also predicted to be in the mammal rather than in the tick, as P66 is not produced by B. burgdorferi in unfed ticks but is expressed during mammalian infection and as the bacteria are acquired by, or transmitted by, the tick (14). P66 expression then correlates with factors specific to mammalian infection.…”
Section: Discussionmentioning
confidence: 96%
“…Gene regulation during the tick phase of the enzootic cycle has come to be recognized as equally important to the spirochete's survival strategy (24,29,32,53,67,73,74,91,92,96). In this regard, recent evidence obtained from expression profiling of p66 and ospD points to the existence of arthropod-specific signals that modulate B. burgdorferi gene expression at various times during the tick phases of the cycle (24,91).…”
mentioning
confidence: 99%
“…It also is now evident, however, that spirochetes must be exposed to as yet unidentified mammalian host-specific signals to induce the full range of transcriptional and translational changes that occur during infection (1,13,17,19,39,97). Gene regulation during the tick phase of the enzootic cycle has come to be recognized as equally important to the spirochete's survival strategy (24,29,32,53,67,73,74,91,92,96). In this regard, recent evidence obtained from expression profiling of p66 and ospD points to the existence of arthropod-specific signals that modulate B. burgdorferi gene expression at various times during the tick phases of the cycle (24,91).…”
mentioning
confidence: 99%